Direct-synthesis method towards copper-containing periodic mesoporous organosilicas: detailed investigation of the copper distribution in the material. Issue 21 (6th May 2015) - Lin, Feng; Meng, Xiangyan; Kukueva, Elena; Altantzis, Thomas; Mertens, Myrjam; Bals, Sara; Cool, Pegie; Van Doorslaer, Sabine
Abstract : A direct synthesis method to incorporate Cu in ethane-bridged PMOs is presented. EPR and TEM reveal the immobilization and distribution of Cu in the material. Abstract : Three-dimensional cubic Fm 3̄ m mesoporous copper-containing ethane-bridged PMO materials have been prepared through a direct-synthesis method at room temperature in the presence of cetyltrimethylammonium bromide as surfactant. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques, including XRD, UV-Vis-Dr, TEM, elemental mapping, continuous-wave and pulsed EPR spectroscopy. The results show that at lower copper loading, the Cu 2+ species are well dispersed in the Cu-PMO materials, and mainly exist as mononuclear Cu 2+ species. At higher copper loading amount, Cu 2+ clusters are observed in the materials, but the distribution of the Cu 2+ species is still much better in the Cu-PMO materials prepared through the direct-synthesis method than in a Cu-containing PMO material prepared through an impregnation method. Moreover, the evolution of the copper incorporation during the PMO synthesis has been followed by EPR. The results show that the immobilization of the Cu 2+ ion/complex and the formation of the PMO materials are taking place simultaneously. The copper ions are found to be situated on the inner surface of the mesopores of the materials and are accessible, which will be beneficial for the catalytic applications.